Privatization in Transition Countries : A Sampling of the Literature - Havrylyshyn, Oleh (IMF Working Papers; Working Paper ;, 1999)
This paper reviews a selection of studies on privatization experiences in transition countries. Empirical studies almost invariably show privatized enterprises outperform state enterprises. Moreover, the literature identifies de novo firms as being clearly the best performers, followed by outsider-dominated firms, while insider-dominated firms are the least efficient among those newly privatized. The importance of de novo firms in enlarging the private sector in transition economies is reviewed, along with the question of whether privatization efforts support or hinder de novo private sector development. Finally, the paper discusses the importance of providing a suitable market environment for successful private-sector development.